A systematic review: adverse events and human talent management in the Latin American hospital context - Araujo-Rosero, Omaira Lucely; Guerrero-Lasso, Paula Andrea; Matabanchoy-Tulcán, Sonia Maritza; Bastidas-Jurado, Claudia Fernanda (Universidad y Salud, 2021)
Introduction: The occurrence of adverse events (AE) is a public health problem that affects patient health status and generates risks for the health personnel, affecting labour wellbeing and leading to accidents, occupational diseases, and unsafe health care procedures. Objective: To determine the most frequent factors when reporting AE and the implications for the human talent management (HTM) in the Latin American hospital context. Materials and methods: A systematic review was carried out by searching articles published between 2009 and 2019 in the BVS, Dialnet, DOAJ, LILACS, MedlinePlus, PubMed, SciELO, ScienceDirect, Redalyc, and EBSCOhost databases. Results: 41 articles were analyzed, identifying both risk and protective factors related to the occurrence of AE, which were grouped within three categories: related to the patients; to the organization; and to the health personnel. Conclusions: EA are complex phenomena that affect health systems. Their causes are associated with multiple factors that are linked to the organization, the health personnel performance, and the behavior of the patients and their families.